Вплив різних методів інсулінотерапії на варіативність глікемічного профілю у дітей, хворих на цукровий діабет 1-го типу - Зелінська, Н. Б.; Глоба, Є. В.; Ніфонтова, Л. В.; Погадаєва, Н. Л. (Clinical Endocrinology and Endocrine Surgery, 2011)
In the article the clinical case of positive clinical experience of continuous subcutaneous insulin infusion effect on glycemic variability in patients with diabetes mellitus type 1 was described. The using of continuous glucose monitoring system may be recommended to all children with diabetes mellitus type 1 for the integrated assessment of glycemic profile and effective correction of treatment.